Recent advances in polymeric nanoparticles for the treatment of hepatic diseases - Feng Gao; Xuefei Feng; Xinyu Li (Frontiers in Pharmacology)
The liver performs crucial roles in energy metabolism, detoxification, and immune regulation. Hepatic diseases, including hepatitis, liver fibrosis, and liver cancer, have posed a significant threat to global health, emphasizing the critical need for the development of novel and effective treatment approaches. Nanotechnology, an emerging technology, has been extensively researched in medicine. Among the many types of nanomaterials, polymeric nanoparticles (NPs) are widely used in drug delivery systems. Compared to traditional therapies, they offer significant advantages in the treatment of liver disease by improving outcomes and reducing side effects. This review introduced the development of liver disease and discussed the application of natural polymers and synthetic polymers in their management. Furthermore, this paper reviewed the application of polymeric nanoparticles -mainly chitosan (CS), hyaluronic acid (HA), polyethylene glycol (PEG) and poly (lactic-co-glycolic acid) (PLGA)-in liver disease treatment, focusing on their use in various delivery systems for pure bioactive compounds of natural origin, drugs, nucleic acids, peptides, and others. Finally, the challenges and future perspectives of the NPs were discussed to provide guidance for further research directions, with the aim of promoting the clinical application of nanotherapeutics in treating hepatic diseases.